Identification of Liver Function Disorders in Pregnant Women at Home Regional Special Hospital for Mother and Child Pertiwi - Inggit Dhiah Asmarani Sudirman; M. Hamsah; Berry Erida Hasbi; Mona Nulanda; Irmayanti Haidir Bima (Jurnal EduHealth, 2025)
Liver function tests need to be carried out on pregnant women, liver function tests to measure enzyme activity in the liver include Serum TestsGlutamate Oxaloacetate Transaminase (SGOT) / Aspartate Transaminase (AST) and Serum Glutamate Pyruvate Transaminase (SGPT) / Alanine Transaminase (ALT) Tests. These examinations can help determine the presence of liver function disorders and can help compile a differential diagnosis. This study was conducted with the aim of early detection of liver dysfunction in pregnant women, using an analytical observational research method with a cross-sectional approach where the data taken was based on primary data at the Pertiwi Mother and Child Special Hospital, and analyzed using SPSS Statistics software. The results showed that the majority of pregnant women who were samples had liver function in the normal category based on the results of Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) examinations. Of the total 30 samples, 96.7% had normal ALT and AST results, while 3.3% showed abnormal results. This shows that liver dysfunction in pregnant women at the Pertiwi Mother and Child Hospital is relatively rare.